2019
DOI: 10.21608/asejaiqjsae.2019.63578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Brackish-Water Treatments on Morphology, Anatomy and Yield Productivity of Wheat (Triticum Aestivum

Abstract: This study included two factors: 1) three irrigation water treatments i) Brackish-water (BW), ii) Magnetic-BW1; brackish water after magnetization through passing a three inch static-magnetic unit produced by Delta Water Company and iii) Magnetic-BW2; brackish water after magnetization through passing a three inch static magnetic unit produced by Magnetic-Technologies Company) and three wheat varieties (Sakha-94, Maser-2 and Gemiza-11). The three irrigation water treatments and the three tested varieties were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The increment in yield of chick pea and yield attributes may be due to the stimulatory role of magnetic treatment in growth parameters, photosynthetic pigment contents, osmoprotectants and total IAA contents in plants under this study (Tables 5, 6). These results are in accordance with those obtained by of [65][66][67][68][69][70] promote water use efficiency, reduced soil pH, and increased available nutrient in several plants. Moreover, MTW induced significant stimulatory effect on mobility and uptake of micronutrient concentration and stimulate growth criteria, consequently all these characters reflected in improving biomass and total yield.…”
Section: Discussionsupporting
confidence: 92%
“…The increment in yield of chick pea and yield attributes may be due to the stimulatory role of magnetic treatment in growth parameters, photosynthetic pigment contents, osmoprotectants and total IAA contents in plants under this study (Tables 5, 6). These results are in accordance with those obtained by of [65][66][67][68][69][70] promote water use efficiency, reduced soil pH, and increased available nutrient in several plants. Moreover, MTW induced significant stimulatory effect on mobility and uptake of micronutrient concentration and stimulate growth criteria, consequently all these characters reflected in improving biomass and total yield.…”
Section: Discussionsupporting
confidence: 92%
“…Magnetized water can improve absorption of nutrients by roots by stimulating root tissue differentiation for the root elongation volume increasing and radicle elongation [ 55 ]. Consequently, magnetic water treatment can improve absorption of water and nutrition in crops and ameliorate the economic properties of crops during later stages [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surendran et al (2016) [ 22 ] showed that the yield of eggplant irrigated with magnetized brackish water improved by 17.0%. Hozayn et al (2019) [ 23 ] indicated that the biological yield, straw yield, and grain yield of wheat under magnetized brackish water irrigation improved by 26.99%, 33.97%, and 19.24%, respectively. In addition, magnetized water irrigation can also improve soil environment and crop stress resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan in C. roseus is important in the biosynthesis of indole alkaloids. The arginine decrease is due to its contribution to chlorophyll biosynthesis, root production, cell division, and polyamide anabolism [62].…”
Section: Hplc Analysis Of Free Amino Acids Phenolic Compounds and Alk...mentioning
confidence: 99%